Technology of turbine plant operating with wet steam proceedings of the international conference organized by the British Nuclear Energy Society in association with the Institution of Mechanical Engineers and the European Nuclear Society, and held in London on 11-13 October 1988. (British Nuclear Energy Society, 1989)
The technology of turbine plant operating with wet steam is a subject of continuing interest and importance, notably in view of the widespread use of wet steam cycles in nuclear power plants and the recent developments of advance low pressure blading for both conventional and wet steam turbine.